A new natural hybrid in Dionysia (Primulaceae) - Zeraatkar, Amin; Khajoei Nasab, Farzaneh (Phytotaxa, 2022)
Dionysia × kowsarana Zeraatkar & Khajoei Nasab, a new natural hybrid that belongs to the family Primulaceae, is described and illustrated. Most of the morphological features of D. × kowsarana sit within the range of its parents. In this study, the morphology, ecology, and geographical distribution, variation of the hybrid are documented.